2004
DOI: 10.1007/s00213-004-2045-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the blockade of ?1-opioid and 5HT2A-serotonergic/?1-noradrenergic receptors on sweet-substance-induced analgesia

Abstract: These data give further evidence for: (a) the involvement of endogenous opioids and a mu1-opioid receptor in the sweet-substance-induced antinociception; (b) the involvement of monoamines and 5HT2A serotonergic/alpha1-noradrenergic receptors in the central regulation of the sweet-substance-produced analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…This mechanism was supported by the observation that sucrose reduces pain sensation when administered orally not when applied via gastric gavage [12,69]. Furthermore, naltrexone and naloxone, opioid antagonists, were shown to abolish the analgesic efect of sweet-tasting solutions [56,[70][71][72] In addition, consuming palatable sweet substances increases endogenous β-endorphin activity in rat brain and in human plasma [69,[73][74][75]. Besides, endogenous opioid system, other neurotransmiters and receptors are probably involved.…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…This mechanism was supported by the observation that sucrose reduces pain sensation when administered orally not when applied via gastric gavage [12,69]. Furthermore, naltrexone and naloxone, opioid antagonists, were shown to abolish the analgesic efect of sweet-tasting solutions [56,[70][71][72] In addition, consuming palatable sweet substances increases endogenous β-endorphin activity in rat brain and in human plasma [69,[73][74][75]. Besides, endogenous opioid system, other neurotransmiters and receptors are probably involved.…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 98%
“…One study revealed a major involvement of nicotinic cholinergic receptors in the sweet substanceinduced analgesia as atropine (cholinergic antagonist) diminished sucrose-induced analgesia [76]. Other studies have shown the involvement of noradrenaline, serotonin and their receptors in the central modulation sweet substance-induced analgesia [71,77,78].…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 99%
“…The involvement of serotonergic and noradrenergic pathways and reticular formation nuclei in the antinociception is reported by works using many noxious stimulus-based tests, such as the tail-flick and hot plate tests (Sawynok and Reid, 1987;Coimbra et al, 1992;Coimbra and Brandão, 1997;Miyase et al, 2005;Rebouças et al, 2005;Segato et al, 2005;Freitas et al, 2005;Kishi et al, 2006;Coimbra et al, 2006), paw-withdrawal latencies (Tsuruoka and Willis, 1996), formalin test (Sajedianfard et al, 2005), percutaneous electrical foot shock (Hirata and Aston-Jones, 1994) and the electrical stimulation of dental pulp test in rats (Couto et al, 1998;Voisin et al, 2005). This last method was used in studies to demonstrate the essential participation of trigeminal nuclei, responsible for the detection of orofacial sensorial innervations originated in the dental pulp and involved in the jaw-opening reflex (Sessle, 1987;Allen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrou-se, em modelos animais, que o efeito analgésico da glicose pode ser revertido com antagonistas de opióides, o que sugere um mecanismo de ação envolvendo a liberação de endorfinas 13 . A revisão do Cochrane Group 14 mostra redução significativa dos indicadores de dor quando a glicose foi usada como analgésico em recém-nascidos prematuros e de termo submetidos à coleta de sangue.…”
Section: Solução Glicosadaunclassified
“…It has been demonstrate, in animal models, that the analgesic effect of glucose can be reversed by opioid antagonists, suggesting a mechanism of action involving the release of endorphins 13 . The revision of the Cochrane Group 14 shows a significant reduction in pain indicators when glucose was used as an analgesic for blood drawing in premature and term newborns.…”
Section: Glucose Solutionmentioning
confidence: 99%